Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água, higiene e saneamento; health / saúde; private sector / setor privado